Composite solid electrolyte, preparation method thereof, positive electrode and lithium ion battery
By surface modification and multi-layer coating of LATP materials in lithium-ion batteries, composite solid electrolytes are formed, which solves the safety problems of liquid electrolytes in lithium-ion batteries and the problem of low interface migration of all-solid state batteries, and realizes the Higher cycle stability and safety performance.
Patent Information
- Application Number
- CN202411615135.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The liquid electrolytes in existing lithium-ion batteries have risks of leakage and spontaneous combustion, and the space charge layer problems caused by the incompatibility of the LATP materials of all-solid lithium metal batteries, low interfacial lithium ion migration number and poor chemical potential of the space charge layer. , it is difficult to take into account both safety performance and circulation performance.
Using a preparation method of composite solid electrolyte, the surface modification of the mixed solution of polyethylene glycol dimethyl ether and amine compounds and the inorganic solid electrolyte LATP is formed to form a three-layer clad LATP composite structure and on its surface. A cationic polymer and metal source are introduced for reduction to form a multi-layer cladding structure.
It improves the interface stability and ion transmission efficiency of the battery, enhances the cycle stability and service life of the battery, and at the same time enhances safety performance, reduces the loss of first discharge capacity, and increases the capacity of the material close to the theoretical value.
Smart Images

Figure BDA0005132631240000221 
Figure BDA0005132631240000231 
Figure BDA0005132631240000241
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite solid electrolyte and a preparation method thereof, a positive electrode and a lithium ion battery. Background Art
[0002] At present, lithium-ion batteries are widely used in electronic devices, electric vehicles and other fields, but liquid electrolytes have the risk of leakage or even spontaneous combustion, and their safety is poor, which limits their further development. All-solid-state lithium metal batteries using inorganic solid electrolytes have the advantages of high safety and high energy density, and are considered to be an effective alternative to lithium-ion batteries. NASICON-type inorganic electrolyte Li1.3Al0.3Ti1.7(PO4)3(LATP) has high lithium ion conductivity, wide electrochemical window and high environmental stability, and is an ideal solid electrolyte material.
[0003] At present, LATP has the advantages of high ionic conductivity, wide electrochemical window and thermal stability. However, the high incompatibility between LATP and lithium metal limits its application. At the same time, the interfacial lithium ion migration number is low. In addition, the huge chemical potential difference between ceramics and electrode materials forms a lithium or sodium depleted space charge layer and the common phenomenon of interface deterioration due to element mutual diffusion and / or reactivity. Therefore, it is difficult to take into account the requirements of safety performance and cycle performance at the same time. At present, the improvement methods for the inherent problems of LATP mainly include oxide coating, such as coating with aluminum oxide, zirconium oxide, etc., or coating with some high molecular polymers. These methods usually reduce the ionic conductivity of the material; using some coating methods to combine multiple materials for composite coating often leads to increased costs and is not conducive to large-scale application.
[0004] Therefore, it is of great significance to develop a composite solid electrolyte with good thermal stability. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a method for preparing a composite solid electrolyte. The composite solid electrolyte provided by the present invention has high rate performance and thermal stability, can improve the interface stability of the battery, enhance the ion transfer efficiency, and overall improve the cycle stability and service life of the battery.
[0006] One aspect of the present invention provides a method for preparing a composite solid electrolyte, comprising:
[0007] A) mixing polyethylene glycol dimethyl ether and an amine compound to obtain a mixed solution; mixing an inorganic solid electrolyte and the mixed solution for a first stirring, reaction, and drying to obtain a surface-modified LATP; the inorganic solid electrolyte is a structure of formula (I):
[0008] Li 1+xAl x Ti 2-x (PO4)3, 0≤x<1;
[0009] B) subjecting the polyethylene glycol dimethyl ether solution, silicon dioxide and lithium salt to a second stirring mixing to obtain a PSE solution;
[0010] C) performing a third stirring mixing of the surface-modified LATP and PSE solution, adjusting the pH value, drying, and calcining to obtain a LATP composite structure with three coating layers;
[0011] D) mixing the LATP composite structure of the three coating layers and the cationic polymer, and stirring to obtain a LATP composite structure with a positive charge;
[0012] E) mixing the metal source, the LATP composite structure with positive charge and the organic solvent aqueous solution, heating and reducing, thereby obtaining the composite solid electrolyte.
[0013] The present invention first prepares a polyethylene glycol dimethyl ether solution; that is, polyethylene glycol dimethyl ether is dissolved in water to obtain a polyethylene glycol dimethyl ether solution; the mass concentration of polyethylene glycol dimethyl ether in the polyethylene glycol dimethyl ether solution is 1% to 5%, and the volume of the polyethylene glycol dimethyl ether solution of the present invention is preferably 100 ml.
[0014] Polyethylene glycol dimethyl ether and amine compounds are mixed to obtain a mixed solution. In the present invention, the added mass of the amine compound is 2% to 6% of the polyethylene glycol dimethyl ether.
[0015] Adding amines to the PEGDME aqueous solution can enhance its interaction with LATP powder.
[0016] In this scheme, LATP is treated with RXNH2 / PEGDME aqueous solution to obtain modified LATP, in which the amino functional group of RXNH2 interacts with the phosphate group and hydroxyl group on the surface of LATP, and can gel and crosslink with the ether polymer to form a three-dimensional network structure; the addition of silicon dioxide particles in the gel process will react with the silanol group (Si-OH) of the amino group of TEA on the surface of LATP to form a silicon-oxygen-nitrogen bond (Si-ON), thereby forming a deposited adhesion layer on the surface of LATP; and the ether polymer has a certain polarity and coordination ability, and can combine with the lithium salt to be uniformly dispersed in the solvent, and the silicon dioxide deposited on the surface of LATP interacts with the lithium salt under high temperature conditions to form LiO y -SiO xThe PEGDME between the silicon dioxide particles also undergoes pyrolysis due to high temperature to achieve a uniform porous inorganic network structure between the particles. Other carbon produced by decomposition will be redeposited on the outermost layer of the LATP surface to form a carbon coating layer, which can inhibit its volume expansion while also increasing the irreversible transformation of amorphous silicon during the first discharge process.
[0017] The inorganic solid electrolyte and the mixed solution are mixed and stirred.
[0018] The above mixing is performed by fully mixing with a magnetic stirrer to ensure that the LATP powder is evenly dispersed in the solution to form a uniform slurry.
[0019] The inorganic solid electrolyte (LATP) of the present invention is of formula (I):
[0020] Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1;
[0021] In some preferred embodiments of the present invention, LATP may be Li 1.8 Al 0.8 Ti 1.2 (PO4)3、Li 1.2 Al 0.2 Ti 1.8 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.1 Al 0.1 Ti 1.9 (PO4)3、Li 1.7 Al 0.7 Ti 1.3 (PO4)3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3.
[0022] The particle size of the inorganic solid electrolyte is 200nm to 500nm;
[0023] Specifically, it may be 200 nm, 216 nm, 237 nm, 260 nm, 350 nm, 423 nm, 500 nm, 280 nm, 263 nm, or any range between the above two values.
[0024] This scheme uses LATP (lithium aluminum titanium phosphate) material, which is an inorganic solid electrolyte with high ionic conductivity. It is superior to garnet-type solid electrolytes in thermal stability and has a wide electrochemical window.
[0025] After the first stirring and mixing, the mixture is allowed to stand, react, and dry to obtain the surface-modified LATP. The first stirring time is 2 to 8 hours; specifically, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours; or a range between any two of the above. After the stirring, the mixture is allowed to stand for 12 to 36 hours.
[0026] The mixed slurry of the present invention is left to stand for a period of time to allow the amine compound and the LATP powder to fully react and form a stable chemical bond. Finally, the aged mixture is placed in an oven for drying to obtain the surface-modified LATP.
[0027] According to the present invention, the polyethylene glycol dimethyl ether is obtained by polymerization of tetraethylene glycol dimethyl ether (G4), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DMDE), and triethylene glycol dimethyl ether (DEGDM);
[0028] The molecular weight of the polyethylene glycol dimethyl ether is 250 to 270 Da;
[0029] The amine compound is ethylenediamine, ethylamine or trimethylamine.
[0030] The added mass of the amine compound of the present invention is 2% to 6% of the polyethylene glycol dimethyl ether; specifically, it can be 2%, 3%, 4%, 5%, 6%; or a range between any two of the above.
[0031] The oven drying temperature of the present invention is 100°C
[0032] In the modification of LATP, PEGDME is first attached to the surface of LATP, and after high-temperature treatment, a thin carbon layer is formed on the surface of LATP, which is beneficial to improving the interface compatibility and contact between LATP and silicate, reducing interface defects and voids, and thus improving the stability and integrity of the entire multilayer structure.
[0033] The polyethylene glycol dimethyl ether solution, silicon dioxide and lithium salt are stirred and mixed to obtain a PSE solution.
[0034] The present invention first prepares a polyethylene glycol dimethyl ether solution; the solvent of the polyethylene glycol dimethyl ether solution is one of dichloromethane or methanol, and the molar ratio of water is (2-5):(5-15). The volume of the polyethylene glycol dimethyl ether solution in the present invention is 50-100 ml.
[0035] For the silicon suboxide SiOx in the present invention, where 0 < x < 2, x can be 0.2, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8; or the range value between any two of the above.
[0036] The particle size of the silicon suboxide is < 5 nm.
[0037] The addition amount of SiOx in the present invention is 5-20% of the mass of LATP, specifically it can be 5%, 7%, 10%, 13%, 15%, 17%, 20%; or the range value between any two of the above.
[0038] The mass ratio of silicon suboxide to PEGDME is 1:(5-30); specifically it can be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30; or the range value between any two of the above.
[0039] According to the present invention, the selected lithium salt is one or more of LiOH·H2O, LiNO3, Li2CO3, LiBOB, LiFSI, LiC2H3O2, and the molar ratio of the lithium salt to the silicon suboxide is (5-9):(6-8);
[0040] The selected second stirring time is 20-60 min, specifically it can be 20 min, 30 min, 40 min, 50 min, 60 min; or the range value between any two of the above. The temperature is 30-50 °C; specifically it can be 30 °C, 40 °C, 50 °C; or the range value between any two of the above.
[0041] The surface-modified LATP and PSE solution are subjected to a third stirring and mixing. The third stirring temperature is 40-60 °C, and the stirring time is 2-5 h.
[0042] The concentration of the polyethylene glycol dimethyl ether solution is preferably 1%-5%; specifically it can be 1%, 2%, 3%, 4%, 5%. The solution volume is 100 ml, and the mass ratio of polyethylene glycol dimethyl ether to the addition amount of LATP is preferably 0.2-1:1.
[0043] After stirring and mixing, the pH value is adjusted. The adjusted pH value is to adjust the pH value to 7-9; more preferably, 28% ammonia water is used to adjust the pH value of the solution to between 7 and 9 to promote the precipitation of silicon suboxide particles on the surface of LATP particles; then the mixed solution with the adjusted pH value is evaporated and dried under the condition of 70-80 °C to form and solidify the gel.
[0044] Finally, the LATP composite gel was calcined at high temperature and then slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0045] The calcination temperature is 400-700°C, specifically 400°C, 500°C, 600°C, 700°C, or any range between the above two. The heating rate is 2-10°C / h, specifically 2°C / h, 3°C / h, 5°C / h, 7°C / h, 10°C / h, or any range between the above two.
[0046] The calcination time is 2 to 6 hours, and can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or any range between any two of the above.
[0047] In some embodiments of the present invention, the calcination temperature is 500° C., the heating rate is 5° C. / h, and the calcination time is 3 h.
[0048] In some embodiments of the present invention, the calcination temperature is 400° C., the heating rate is 3° C. / h, and the calcination time is 3 hours.
[0049] In some embodiments of the present invention, the calcination temperature is 600° C., the heating rate is 7° C. / h, and the calcination time is 5 h.
[0050] In some embodiments of the present invention, the calcination temperature is 500° C., the heating rate is 2° C. / h, and the calcination time is 5 h.
[0051] In some embodiments of the present invention, the calcination temperature is 700° C., the heating rate is 3° C. / h, and the calcination time is 5 h.
[0052] In some embodiments of the present invention, the calcination temperature is 400° C., the heating rate is 8° C. / h, and the calcination time is 5 h.
[0053] In some embodiments of the present invention, the calcination temperature is 500° C., the heating rate is 5° C. / h, and the calcination time is 3 h.
[0054] In some embodiments of the present invention, the calcination temperature is 400° C., the heating rate is 2° C. / h, and the calcination time is 2 h.
[0055] The LATP composite structure with three coating layers and the cationic polymer are mixed and stirred to obtain a LATP composite structure with positive charge. The mixture is stirred in an ultrasonic bath at room temperature for 5 to 10 minutes, ultrasonically cleaned 2 to 3 times to remove excess PDDA, and dried to obtain a powder.
[0056] In the present invention, the cationic polymer is selected from polyethyleneimine (PEI), polydiallyldimethylammonium chloride (PDDA), chitosan or polylysine.
[0057] The weight average molecular weight (Mw) of the cationic polymer is less than 100 kg mol -1 The amount of cationic polymer added is 5-20% of LATP; specifically, it can be 5%, 7%, 10%, 13%, 15%, 17%, 20%; or a range between any two of the above.
[0058] This scheme uses cationic polymers to modify the carbon coating of LATP, and the carbon coating provides additional chemically active sites for adsorbing the cationic polymer layer. Nano alloys or elemental metals are synthesized on the surface of LATP using the polyol method. Polyol metal salts dissociate negatively charged ions in the solution, and negatively charged oligomers tend to migrate and deposit on the positively charged cationic polymer layer, which plays a role in the adsorption and dispersion of metal ions on its surface. The cationic polymer layer serves as a scaffold for the composite shell, and a continuous and compact composite shell can also be formed using this method. At the same time, since a large number of hydrogen bonds carried by hydroxyl groups in the polyol are selectively adsorbed on the low barrier surface, this increases the exposure rate of the main lithium ion channel, thereby increasing the Li+ migration rate of the material and reducing the Li+ migration impedance on the LATP surface. At the same time, low-polarization nano alloys can guide the uniform deposition of lithium ions and effectively inhibit the formation of lithium dendrites, thereby improving the safety and cycle stability of the battery, and further enhancing the performance and application value of LATP.
[0059] The metal source, the LATP composite structure with positive charge and an organic solvent aqueous solution are mixed, heated and reduced to obtain the product.
[0060] The metal source of the present invention is an acetylacetonate metal salt; the acetylacetonate metal salt comprises a mixture of at least one acetylacetonate of Ni, Co, Mn, Fe, Cu, Pb, Ru and Mo and lithium acetylacetonate; the mass ratio of the mixture of at least one acetylacetonate of Ni, Co, Mn, Fe, Cu, Pb, Ru and Mo and lithium acetylacetonate is 1:(1-2);
[0061] The mass ratio of lithium acetylacetonate to LATP in the present invention is 0.3 to 1:1.
[0062] The selected organic solvents are TEG, ethylene glycol, propylene glycol, and IPA. The volume of the organic solvent aqueous solution is 100 ml, wherein the ratio of the organic solvent to water is (1-2.5): (1-2.5); specifically, it can be 2.5:1, 1.5:1, 1:1, 1:1.5, and 1:2.5.
[0063] The heating is carried out in a gas environment, wherein the gas includes a mixture of argon or nitrogen and hydrogen; the heating starts at 30°C, and the heating rate is 5-10 Kmin -1 , heating to 200-300° C. for reflux reaction, wherein the reflux time is 1-5 h.
[0064] The present invention firstly reacts LATP with PEGDME and an amine compound (R X NH2) aqueous solution, and then X NH2 reacts with lithium ions on the surface of LATP to form R X NH2-Li and PEGDME are attached to the surface of LATP, and then silicon oxide and lithium salt are dissolved in EGDME solution respectively, and then cross-linked with the treated LATP to form a gel composite structure. After high-temperature treatment, a pre-lithiated silicon oxide porous inorganic network structure is obtained, and the remaining carbon is deposited on the surface of LATP and silicon oxide layer to form carbon coating layers to varying degrees, which improves the electrical conductivity of the material and provides a stable chemical and electrochemical reaction interface; finally, cationic polymers are introduced on the surface of LATP, and the cationic polymer monolayer adsorbed on the surface of LATP becomes the basic structure of the outer shell, and provides nucleation sites for the growth of ordered alloy nanoparticles in a hybrid manner, and finally forms a multi-layer coating layer: from the inside to the outside, it is a thin carbon layer, a silicon oxide layer, a carbon layer, and a multi-layer coating layer structure of an alloy hybrid shell.
[0065] Since there are no chemical bonds between nano-metal alloy particles, cationic polymers have a strong binding force to nano-metal alloys or nano-metal particles, and alloy nanoparticles are preferentially in the cationic polymer layer. Therefore, the hybrid structure of metal alloys and polymer chains stabilizes the three-dimensional network structure on the surface of LATP, thereby forming a nanocomposite shell. The three-dimensional alloy layer provides higher thermal stability, electrical conductivity, chemical stability and mechanical strength than other coating layers under high temperature environments. At the same time, by utilizing its compatibility and corrosion resistance with the electrolyte, it can prevent harmful substances in the electrolyte from further corroding the carbon coating layer, thereby ensuring the stability of the overall coating structure.
[0066] The three-dimensional structure-core-shell LATP based on this scheme is applied to positive electrode coating. It can improve the interface stability of the battery, enhance the ion transmission efficiency, improve the rate performance and thermal stability, and improve the cycle stability and service life of the battery as a whole. At the same time, it also enhances the safety of LATP, thereby achieving the performance requirements of improving the energy density and power density of the battery.
[0067] The present invention provides a composite solid electrolyte prepared by the preparation method described in any one of the above technical solutions.
[0068] This scheme prepares a composite solid electrolyte with multiple coating layers, in which the core is LATP, and the thin carbon layer on the surface of LATP has a porous structure, which helps the diffusion of ions on the surface of the material and improves the efficiency of ion transmission. In the case of battery overcharge or other abnormal conditions, the thin carbon layer can be used as a sacrificial layer and is consumed first, thereby protecting the more valuable LATP.
[0069] The inorganic carbon network structure deposited during the pre-lithiation of silicon dioxide in this scheme facilitates a more uniform reaction between the lithium salt and SiOx, thereby forming a favorable LiOy-Si0x, which significantly reduces the first irreversible capacity loss and increases the capacity of the material close to the theoretical value.
[0070] The porous network layer structure of silicon oxide in this scheme has the advantages of low density, high specific strength, high specific surface area, etc., which increases the spatial position of lithium insertion during discharge to improve the lithium insertion capacity. At the same time, the porous tunnel structure can provide a lower lithium ion diffusion barrier and enhance the diffusion kinetics of Li+ at the electrode / electrolyte interface, thereby improving the battery's cycle stability and ICE. The silicon oxide layer embedded in the coating layer can effectively absorb the volume expansion during the charge and discharge process, enhancing the mechanical stability of LATP. The SiOx layer can improve the interface compatibility between LATP and other battery components, reduce stress and cracking at the interface, thereby reducing the interface resistance and forming an interface layer with high ionic conductivity and high migration number.
[0071] In this scheme, LATP is wrapped by a carbon layer to provide additional protection, reduce the erosion and damage of the external environment (such as water and oxygen), and maintain its stable performance; at the same time, together with other coating layers, it blocks the direct impact of external mechanical stress, physical collision and possible chemical erosion on the structure, and prevents LATP from being directly subjected to excessive stress and causing lattice distortion, cracks or breakage. The rough surface of the carbon layer promotes the contact between lithium ions and the silicon oxide layer, improves the conductivity of the silicon oxide layer, and thus improves the electrochemical reactivity.
[0072] The stable three-dimensional alloy structure layer of this scheme gives the LATP surface a three-dimensional network structure, providing rich and continuous ion transmission channels to improve ion conductivity while guiding the uniform deposition of lithium ions, effectively inhibiting the formation of lithium dendrites; when the battery is charged and discharged, the alloy hybrid shell can work synergistically with the carbon layer to evenly distribute the stress caused by the volume change of the silicon oxide layer, reduce local stress concentration, and improve the electrochemical performance of the battery.
[0073] In this scheme, the alloy material introduced by the cationic polymer can be used as an additional lithium source during the charge and discharge process to undergo reversible alloying and de-golding reactions with the lithium ions of LATP, thereby improving the initial coulombic efficiency of the battery. The alloy also serves as a protective structure for the carbon layer, preventing the carbon layer from mechanical wear, chemical corrosion and electrochemical damage, thereby extending the service life of the battery and improving its safety.
[0074] The alloy layer of this scheme provides the LATP material with excellent thermal stability, electrical conductivity and chemical stability at high temperatures, reduces safety risks caused by material degradation or thermal runaway, and extends the service life of the battery.
[0075] This scheme provides a composite solid electrolyte with a multi-coating structure, which has excellent ionic conductivity and excellent interface compatibility, and can effectively inhibit volume expansion and ensure the stability of the solid electrolyte structure. When this composite solid electrolyte is used to coat the positive electrode material and applied in the lithium battery, it can significantly improve the specific capacity and conductivity of the positive electrode material, increase the available lithium content, and thus greatly improve the energy density of the battery, which is difficult to achieve with many other solid electrolytes. The significant difference from other solid electrolytes is that its unique multi-coating structure can effectively wrap the active position or sensitive components, greatly reducing the direct contact with the external environment, thereby effectively limiting the amplitude of volume change, and at the same time providing certain mechanical support to prevent excessive expansion of the internal material, which helps to maintain the stability of the entire system structure and reduce the structural damage caused by volume change. In addition, the composite solid electrolyte prepared by this scheme has lower interface impedance and higher thermal stability, and its interface is more stable than other solid electrolytes, reducing or thermal runaway safety risks, and extending the service life of the battery, thereby well meeting the urgent needs of modern electronic equipment and electric vehicles for high energy density batteries, which is also a feature that many other solid electrolytes rarely have. Therefore, the positive electrode material containing this multi-coating solid electrolyte prepared in this scheme can achieve a variety of key technical effects in lithium battery applications.
[0076] The present invention has clearly described the above specific preparation method, which will not be repeated here.
[0077] The present invention provides a positive electrode, comprising a positive electrode material, a conductive agent, a binder and the composite solid electrolyte described in the above technical solution.
[0078] The present invention firstly dry-mixes the positive electrode material, the conductive agent and the binder in a mass ratio of (80-70):(10-20):10, adds an organic solvent to prepare a positive electrode slurry, coats the positive electrode current collector, and slices the positive electrode material sheet after drying.
[0079] The positive electrode material selected by the present invention is in Represents different selected metal elements, R is selected from at least one element of Ni, Co, Fe, Al, Ti, Mo
[0080] Among them, 0<x≤1, 0≤y<1, 0<z≤1, 1≤s≤4.
[0081] The cathode material of the present invention can be Li 1.3 Ni 0.35 Mn 0.65 O2, Li1.03(Mn0.6Co0.35Ni0.05)0.97O2, Li1.1(Ni0.4Co0.4)1.3Mn0.6O1.8, Li1.05(Mn0.8Fe0.2)0.9O2, Li1.02(Fe0.2Mn0.8)0.96O2, Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2、Li 1.19 (Ni 0.4 Co 0.4 ) 1.3 Mn 0.6 O 1.8
[0082] The selected binder is any one or at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and hydroxypropyl methylcellulose. The selected organic solvent is NMP, anhydrous ethanol, and acetone; and the selected conductive agent is any one or at least two of graphite, carbon black, and activated carbon.
[0083] The prepared composite solid electrolyte is dispersed in an organic solvent and magnetically stirred for a sufficient time to form a miscible solution. All processes are carried out in a glove box. The selected organic solvents are NMP, anhydrous ethanol, and acetone; the selected stirring time is 12 to 36 hours; the mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is uniformly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film, and the organic solvent is removed by heating at 120°C to obtain a positive electrode composite material with a solid electrolyte film attached. The thickness of the composite film is 8 to 50 μm.
[0084] The present invention provides a lithium ion battery, comprising the positive electrode, negative electrode, separator and electrolyte described in the above technical solution.
[0085] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte involved in the above technical solution. The active material of the negative electrode is preferably selected from any one of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide. The diaphragm is selected from one of a polypropylene diaphragm and a polyethylene diaphragm, and the present invention preferably selects a polyethylene diaphragm.
[0086] The lithium ion battery made by the electrolyte of the present invention has a charge and discharge voltage of 3.0 to 4.6 V, and significantly improves the rate performance and cycle life of the battery at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 Schematic diagram of the solid electrolyte structure of the present invention, from the outside to the inside, the structure is an alloy hybrid shell, a thick carbon layer, a pre-lithiation silicon layer, a thin carbon layer, and a solid electrolyte;
[0088] Figure 2 for Figure 1 TEM image of the structural schematic diagram, the structure from the outside to the inside is alloy hybrid shell, thick carbon layer, pre-lithiation silicon layer, thin carbon layer, and solid electrolyte. DETAILED DESCRIPTION
[0089] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] In this application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.
[0091] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0092] Furthermore, the terms “first”, “second”, etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance.
[0093] In order to further illustrate the present invention, the following examples are provided for detailed description. In the following examples of the present invention, if no specific conditions are specified, the conditions may be carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products available on the market.
[0094] Example 1
[0095] 1. Material preparation
[0096] 1. Weigh 5g G4 and dissolve it in an appropriate amount of 95ml deionized water to form a 5% G4 aqueous solution, then weigh 0.3g ethylenediamine and dissolve it in the above solution. Finally, slowly add 5g Li1.8Al0.8Ti1.2(PO4)3 powder with a median particle size of 237nm to the above solution, and stir it with a magnetic stirrer for 3h to form a uniform slurry; the mixed slurry is allowed to stand at 50℃ for 20h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0097] 2. Mix 23.08 ml methanol and 76.92 ml deionized water to form a mixed solvent. Dissolve 5 g G4 in the mixed solvent to form a uniform solution. Add 0.57 g SiO0.2 and 0.98 g LiFSI in turn and mix well. Stir at 40 ° C for 30 minutes to form a stable solution system, referred to as (PSE)
[0098] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 55°C for 4 hours, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 500°C at a rate of 5°C / h and calcined at a high temperature for 3 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0099] 4. Mix the prepared LATP complex aqueous dispersion (40 mL) with 0.38 g PEI aqueous solution (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it 3 times to remove excess PEI. Finally, dry it.
[0100] 6. Dissolve lithium acetylacetonate (1.1 g), cobalt acetylacetonate (2.63 g) and PEI-modified LATP complex in 100 ml TEG (71.43 ml) aqueous solution, mix and stir evenly, and then heat at 10 K min -1 The heating rate was stirred and heated from 30°C, refluxed in gas (Ar / H2) for 2h, and the temperature was stabilized at 250°C. After the reaction was completed, the solution was cooled to room temperature. The powder sample was obtained by centrifugal precipitation and washing the precipitate with ethanol several times.
[0101] 2. Preparation of positive electrode materials
[0102] 1. Li 1.3 Ni 0.35 Mn0.65 O2, graphite and PVDF were dry-mixed in a mass ratio of 75:15:10, and NMP was added to prepare a positive electrode slurry, which was coated on the positive electrode current collector and then dried and sliced into positive electrode material sheets. The prepared composite solid electrolyte was dispersed in NMP and magnetically stirred for 20 hours to form a mixed solution. All processes were carried out in a glove box.
[0103] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 30um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0104] Example 2
[0105] 1. Material preparation
[0106] 1. Weigh 4g DME and dissolve it in an appropriate amount of 96ml deionized water to form a 4% DME aqueous solution, then weigh 0.18g ethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.2Al0.2Ti1.8(PO4)3 powder with a median particle size of 216nm to the above solution, and stir it with a magnetic stirrer for 6h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 18h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0107] 2. Mix 14.3 ml of dichloromethane and 35.7 ml of deionized water to form a mixed solvent. Dissolve 10.8 g of DME in the mixed solvent to form a uniform solution. Add 0.37 g of SiO0.6 and 1.05 g of LiNO3 in turn, mix well, and stir at 30 ° C for 38 minutes to form a stable solution system, referred to as (PSE)
[0108] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 40°C for 3h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 400°C at a rate of 3°C / h and calcined at a high temperature of 3 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0109] 4. Mix the prepared aqueous dispersion of LATP complex (40 mL) with an aqueous solution of 0.38 g polylysine (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it three times to remove excess polylysine. Finally, dry it.
[0110] 6. Dissolve lithium acetylacetonate (0.8 g), nickel acetylacetonate (3.06 g) and polylysine-modified LATP complex in 100 ml of ethylene glycol (60 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 8 K min-1 from 30 ° C, reflux in gas (Ar / H2) for 3 h, and stabilize the temperature at 200 ° C. After the reaction is completed, the solution is cooled to room temperature. The precipitate is centrifuged and then washed with ethanol several times to obtain a powder sample.
[0111] 2. Preparation of positive electrode materials
[0112] 1. Li1.03(Mn0.6Co0.35Ni0.05)0.97O2, graphite and SBR were dry-mixed in a mass ratio of 80:10:10, and anhydrous ethanol was added to prepare a positive electrode slurry, which was coated on the positive electrode collector and sliced into positive electrode material sheets after drying; the prepared composite solid electrolyte was dispersed in anhydrous ethanol and magnetically stirred for 18 hours to form a mixed solution. All processes were carried out in a glove box.
[0113] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 30um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0114] Example 3
[0115] 1. Material preparation
[0116] 1. Weigh 4g DMDE and dissolve it in an appropriate amount of 96ml deionized water to form a 4% DMDE aqueous solution, then weigh 0.08g ethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.4Al0.4Ti1.6(PO4)3 powder with a median particle size of 350nm to the above solution, and stir it with a magnetic stirrer for 8h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 15h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0117] 2. Mix 20 ml of dichloromethane and 60 ml of deionized water to form a mixed solvent. Dissolve 16.7 g of DMDE in the mixed solvent to form a uniform solution. Add 0.43 g of SiO0.8 and 0.84 g of LiNO3 in turn and mix well. Stir at 47 ° C for 50 minutes to form a stable solution system, referred to as (PSE)
[0118] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 50°C for 2h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 600°C at 7°C / h and calcined at a high temperature for 5 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0119] 4. Mix the prepared aqueous dispersion of LATP complex (40 mL) with an aqueous solution of 0.38 g PDDA (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it three times to remove excess PDDA. Finally, dry it.
[0120] 6. Dissolve lithium acetylacetonate (0.74 g), cobalt acetylacetonate (2.63 g) and PDDA-modified LATP complex in 100 ml TEG (50 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 7 K min-1 from 30 ° C, reflux in gas (N2 / H2) for 1 h, and stabilize the temperature at 240 ° C. After the reaction, cool the solution to room temperature. Centrifuge and wash the precipitate several times with ethanol to obtain a powder sample.
[0121] 2. Preparation of positive electrode materials
[0122] 1. Li1.1(Ni0.4Co0.4)1.3Mn0.6O1.8, carbon black and PAA were dry-mixed in a mass ratio of 72:18:10, and acetone was added to prepare a positive electrode slurry, which was coated on the positive electrode current collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in acetone and magnetically stirred for 20 hours to form a mixed solution. All processes were carried out in a glove box.
[0123] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 10um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0124] Example 4
[0125] 1. Material preparation
[0126] 1. Weigh 3g DMDE and dissolve it in an appropriate amount of 97ml deionized water to form a 3% DMDE aqueous solution, then weigh 0.15g trimethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.1Al0.1Ti1.9(PO4)3 powder with a median particle size of 423nm to the above solution, and stir it with a magnetic stirrer for 4h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 30h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0127] 2. Mix 14.3 ml methanol and 35.7 ml deionized water to form a mixed solvent. Dissolve 8.7 g DMDE in the mixed solvent to form a uniform solution. Add 0.82 g SiO0.6 and 1.43 g Li2CO3 in turn and mix well. Stir at 45°C for 40 minutes to form a stable solution system, referred to as (PSE).
[0128] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 60°C for 4 hours, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 500°C at a rate of 2°C / h and calcined at a high temperature of 500°C for 5 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0129] 4. Mix the prepared LATP complex aqueous dispersion (30 mL) with 0.54 g PEI aqueous solution (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it 3 times to remove excess PEI. Finally, dry it.
[0130] 6. Dissolve lithium acetylacetonate (0.67 g), manganese acetylacetonate (1.55 g) and PEI-modified LATP complex in 100 ml propylene glycol (40 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 5 K min-1 from 30 ° C, reflux in gas (Ar / H2) for 4 h, and stabilize the temperature at 280 ° C. After the reaction, cool the solution to room temperature. Centrifuge and wash the precipitate several times with ethanol to obtain a powder sample.
[0131] 2. Preparation of positive electrode materials
[0132] 1. Li1.05(Mn0.8Fe0.2)0.9O2, carbon black and PAA were dry-mixed in a mass ratio of 79:11:10, and NMP was added to prepare a positive electrode slurry, which was coated on the positive electrode current collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in NMP and magnetically stirred for 30 hours to form a mixed solution. All processes were carried out in a glove box.
[0133] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 9um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0134] Example 5
[0135] 1. Material preparation
[0136] 1. Weigh 2g G4 and dissolve it in an appropriate amount of 98ml deionized water to form a 2% G4 aqueous solution, then weigh 0.1g ethylenediamine and dissolve it in the above solution. Finally, slowly add 5g Li1.7Al0.7Ti1.3(PO4)3 powder with a median particle size of 260nm to the above solution, and stir it with a magnetic stirrer for 3h to form a uniform slurry; the mixed slurry is allowed to stand at 50℃ for 25h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0137] 2. Mix 16.2 ml methanol and 53.8 ml deionized water to form a mixed solvent. Dissolve 15.7 g G4 in the mixed solvent to form a uniform solution. Add 0.95 g SiO1.2 and 2.01 g LiC2H3O2 in turn and mix well. Stir at 40°C for 30 minutes to form a stable solution system, referred to as (PSE).
[0138] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 40°C for 4 hours, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 700°C at a rate of 3°C / h and calcined at a high temperature of 700°C for 5 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0139] 4. Mix the prepared aqueous dispersion of LATP complex (30 mL) with an aqueous solution of 0.64 g polylysine (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it three times to remove excess polylysine. Finally, dry it.
[0140] 6. Dissolve lithium acetylacetonate (0.8 g), cobalt acetylacetonate (1.77 g) and polylysine-modified LATP complex in 100 ml IPA (28.57 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 6 K min-1 from 30 ° C, reflux in gas (N2 / H2) for 5 h, and stabilize the temperature at 300 ° C. After the reaction is completed, the solution is cooled to room temperature. The precipitate is centrifuged and then washed with ethanol several times to obtain a powder sample.
[0141] 2. Preparation of positive electrode materials
[0142] 1. Li1.03(Mn0.6Co0.35Ni0.05)0.97O2, graphite and SBR were dry-mixed in a mass ratio of 73:17:10, and acetone was added to prepare a positive electrode slurry, which was coated on the positive electrode collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in acetone and magnetically stirred for 35 hours to form a mixed solution. All processes were carried out in a glove box.
[0143] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 18um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0144] Example 6
[0145] 1. Material preparation
[0146] 1. Weigh 1g DEGDM and dissolve it in an appropriate amount of 99ml deionized water to form a 1% DEGDM aqueous solution, then weigh 0.08g ethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.3Al0.3Ti1.7(PO4)3 powder with a median particle size of 500nm to the above solution, and stir it with a magnetic stirrer for 5h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 36h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0147] 2. Mix 25 ml of dichloromethane and 75 ml of deionized water to form a mixed solvent. Dissolve 8.7 g of DEGDM in the mixed solvent to form a uniform solution. Add 0.65 g of SiO1.4 and 0.79 g of LiOH·H2O in turn and mix well. Stir at 36°C for 53 minutes to form a stable solution system, referred to as (PSE).
[0148] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 60°C for 5h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 400°C at 8°C / h and calcined at a high temperature for 5 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0149] 4. Mix the prepared LATP complex aqueous dispersion (50 mL) with 0.88 g PDDA aqueous solution (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it 3 times to remove excess PDDA. Finally, dry it.
[0150] 6. Dissolve lithium acetylacetonate (1.21 g), molybdenum acetylacetonate (4.28 g) and PDDA-modified LATP complex in 100 ml TEG (60 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 10 Kmin-1 from 30 ° C, reflux in gas (Ar / H2) for 4 h, and stabilize the temperature at 220 ° C. After the reaction, cool the solution to room temperature. Centrifuge and wash the precipitate several times with ethanol to obtain a powder sample.
[0151] 2. Preparation of positive electrode materials
[0152] 1. Li1.3Ni0.35Mn0.65O2, activated carbon and hydroxypropyl methylcellulose were dry-mixed in a mass ratio of 75:15:10, and NMP was added to prepare a positive electrode slurry, which was coated on the positive electrode current collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in NMP and magnetically stirred for 25 hours to form a mixed solution. All processes were carried out in a glove box.
[0153] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 25 um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0154] Example 7
[0155] 1. Material preparation
[0156] 1. Weigh 5g DMDE and dissolve it in an appropriate amount of 95ml deionized water to form a 5% DMDE aqueous solution, then weigh 0.3g ethylenediamine and dissolve it in the above solution. Finally, slowly add 5g Li1.3Al0.3Ti1.7(PO4)3 powder with a median particle size of 280nm to the above solution, and stir it with a magnetic stirrer for 7h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 22h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0157] 2. Mix 27.6 ml methanol and 52.4 ml deionized water to form a mixed solvent. Dissolve 6 g DMDE in the mixed solvent to form a uniform solution. Add 0.2 g SiO and 0.35 g LiC2H3O2 in turn and mix well. Stir at 50°C for 47 minutes to form a stable solution system, referred to as (PSE).
[0158] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 48°C for 2h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 500°C at a rate of 5°C / h and calcined at a high temperature for 3 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0159] 4. Mix the prepared aqueous dispersion of LATP complex (45 mL) with an aqueous solution of 0.92 g chitosan (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it three times to remove excess chitosan. Finally, dry it.
[0160] 6. Dissolve lithium acetylacetonate (1.45 g), copper acetylacetonate (3.58 g) and chitosan-modified LATP complex in 100 ml of propylene glycol (40 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 8 Kmin-1 from 30 ° C, reflux in gas (N2 / H2) for 5 h, and stabilize the temperature at 280 ° C. After the reaction is completed, the solution is cooled to room temperature. The precipitate is centrifuged and then washed with ethanol several times to obtain a powder sample.
[0161] 2. Preparation of positive electrode materials
[0162] 1. Li1.1(Ni0.4Co0.4)1.3Mn0.6O1.8, activated carbon and PVDF were dry-mixed in a mass ratio of 77:13:10, and NMP was added to prepare a positive electrode slurry, which was coated on the positive electrode current collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in NMP and magnetically stirred for 30 hours to form a mixed solution. All processes were carried out in a glove box.
[0163] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 20um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0164] Example 8
[0165] 1. Material preparation
[0166] 1. Weigh 1g DME and dissolve it in an appropriate amount of 99ml deionized water to form a 1% DME aqueous solution, then weigh 0.05g ethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.4Al0.4Ti1.6(PO4)3 powder with a median particle size of 200nm to the above solution, and stir it with a magnetic stirrer for 2h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 12h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0167] 2. Mix 12.5 ml methanol and 37.5 ml deionized water to form a mixed solvent. Dissolve 5 g DME in the mixed solvent to form a uniform solution. Add 0.25 g SiO and 0.28 g LiC2H3O2 in turn and mix well. Stir at 30°C for 20 min to form a stable solution system, referred to as (PSE).
[0168] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 40°C for 2h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 400°C at a rate of 2°C / h and calcined at a high temperature of 2 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0169] 4. Mix the prepared LATP complex aqueous dispersion (40 mL) with 0.1 g PDDA aqueous solution (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it 3 times to remove excess PDDA. Finally, dry it.
[0170] 6. Dissolve lithium acetylacetonate (0.5 g), cobalt acetylacetonate (0.18 g) and PDDA-modified LATP complex in 100 ml of ethylene glycol (71.43 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 5 Kmin-1 from 30 ° C, reflux in gas (Ar / H2) for 1 h, and stabilize the temperature at 200 ° C. After the reaction is completed, the solution is cooled to room temperature. The precipitate is centrifuged and then washed with ethanol several times to obtain a powder sample.
[0171] 2. Preparation of positive electrode materials
[0172] 1. Li1.02(Fe0.2Mn0.8)0.96O2, graphite and hydroxypropyl methylcellulose were dry-mixed in a mass ratio of 70:20:10, and NMP was added to form a positive electrode slurry, which was coated on the positive electrode current collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in NMP and magnetically stirred for 12 hours to form a mixed solution. All processes were carried out in a glove box.
[0173] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 8um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0174] Example 9
[0175] 1. Material preparation
[0176] 1. Weigh 5g DME and dissolve it in an appropriate amount of 95ml deionized water to form a 5% DME aqueous solution, then weigh 0.27g ethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.4Al0.4Ti1.6(PO4)3 powder with a median particle size of 263nm to the above solution, and stir it with a magnetic stirrer for 3h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 20h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0177] 2. Mix 37.5 ml of dichloromethane and 60.5 ml of deionized water to form a mixed solvent. Dissolve 21.2 g of DMDE in the mixed solvent to form a uniform solution. Add 1 g of SiO and 2.36 g of LiFSI in turn and mix well. Stir at 40 ° C for 60 min to form a stable solution system, referred to as (PSE).
[0178] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 60°C for 2h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 650°C at 6°C / h and calcined at a high temperature for 2 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0179] 4. Mix the prepared LATP complex aqueous dispersion (20 mL) with 0.61 g PEI aqueous solution (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it 3 times to remove excess PEI. Finally, dry it.
[0180] 6. Dissolve lithium acetylacetonate (1.5 g), nickel acetylacetonate (0.58 g) and PEI-modified LATP complex in 100 ml propylene glycol (71.43 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 7 Kmin-1 from 30 ° C, reflux in gas (N2 / H2) for 3 h, and stabilize the temperature at 250 ° C. After the reaction is completed, the solution is cooled to room temperature. The precipitate is centrifuged and then washed with ethanol several times to obtain a powder sample.
[0181] 2. Preparation of positive electrode materials
[0182] 1. Li1.1(Ni0.4Co0.4)1.3Mn0.6O1.8, graphite and hydroxypropyl methylcellulose were dry-mixed in a mass ratio of 74:16:10, and anhydrous ethanol was added to form a positive electrode slurry, which was coated on the positive electrode current collector, dried and sliced into positive electrode material sheets; the prepared composite solid electrolyte was dispersed in anhydrous ethanol and magnetically stirred for 36 hours to form a mixed solution. All processes were carried out in a glove box.
[0183] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 45um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0184] Example 10
[0185] 1. Material preparation
[0186] 1. Weigh 5g G4 and dissolve it in an appropriate amount of 95ml deionized water to form a 5% G4 aqueous solution, then weigh 0.3g trimethylamine and dissolve it in the above solution. Finally, slowly add 5g Li1.4Al0.4Ti1.6(PO4)3 powder with a median particle size of 500nm to the above solution, and stir it with a magnetic stirrer for 8h to form a uniform slurry; the mixed slurry is allowed to stand at 50°C for 36h to form a stable chemical bond. Finally, the aged mixture is placed in an oven to dry to obtain surface-modified LATP
[0187] 2. Mix 28.57 ml methanol and 71.43 ml deionized water to form a mixed solvent. Dissolve 30 g G4 in the mixed solvent to form a uniform solution. Add 1 g SiO and 1.13 g LiC2H3O2 in turn and mix well. Stir at 40 ° C for 60 minutes to form a stable solution system, referred to as (PSE).
[0188] 3. The prepared modified LATP and PSE solution were mixed and stirred at a constant temperature of 60°C for 5h, and the pH value of the solution was adjusted to between 7 and 9 using 28% ammonia water (NH3 aqueous solution), and then the mixed solution with the adjusted pH value was evaporated and dried at 70-80°C to form and solidify the gel. Finally, the LATP composite gel was heated to 700°C at a rate of 10°C / h and calcined at a high temperature of 700°C for 6 hours, and finally slowly cooled to 25°C to obtain a LATP composite structure with three coating layers.
[0189] 4. Mix the prepared aqueous dispersion of LATP complex (50 mL) with an aqueous solution of 1 g PEI (25 mL). Stir the mixture in an ultrasonic bath at room temperature for 10 minutes and ultrasonically clean it 3 times to remove excess PEI. Finally, dry it.
[0190] 6. Dissolve lithium acetylacetonate (1.5 g), cobalt acetylacetonate (0.64 g) and PEI-modified LATP complex in 100 ml IPA (40 ml) aqueous solution and stir evenly, then stir and heat at a heating rate of 10 K min-1 from 30 ° C, reflux in gas (Ar / H2) for 5 h, and stabilize the temperature at 300 ° C. After the reaction is completed, the solution is cooled to room temperature. The precipitate is centrifuged and then washed with ethanol several times to obtain a powder sample.
[0191] 2. Preparation of positive electrode materials
[0192] 1. Li1.02(Fe0.2Mn0.8)0.96O2, carbon black and PAA were dry-mixed in a mass ratio of 80:10:10, and anhydrous ethanol was added to form a positive electrode slurry, which was coated on the positive electrode current collector. After drying, the slurry was sliced into positive electrode material sheets. The prepared composite solid electrolyte was dispersed in anhydrous ethanol and magnetically stirred for 36 hours to form a mixed solution. All processes were carried out in a glove box.
[0193] 2. The mixed solution obtained above is coated on the prepared positive electrode material sheet, and the mixed solution is evenly attached to the surface of the positive electrode material sheet to form a thin layer of liquid film with a thickness of 50um, and then heated at 120°C to remove the organic solvent to obtain a positive electrode composite material with a solid electrolyte film attached.
[0194] Comparative Example 1
[0195] The carbon-coated LATP composite solid electrolyte was prepared according to CN110858642B, and the testing method was the same.
[0196] Comparative Example 2
[0197] Compared with Example 1, during the gelation process of Li1.8Al0.8Ti1.2(PO4)3, silicon dioxide and lithium salt are not added, and the rest are the same.
[0198] Comparative Example 3
[0199] Compared with Example 3, after Li1.4Al0.4Ti1.6(PO4)3 gel is formed, the carbon coating layer is not formed by high-temperature calcination, and the rest is the same.
[0200] Comparative Example 4
[0201] Compared with Example 3, Li1.4Al0.4Ti1.6(PO4)3 gel is calcined at high temperature to form a LATP composite structure with three coating layers, and no alloy hybrid shell is introduced on its surface, and the rest is the same.
[0202] Comparative Example 5
[0203] Compared with Example 3, Li1.4Al0.4Ti1.6(PO4)3 was not subjected to surface modification, and the rest was the same.
[0204] Comparative Example 6
[0205] Compared with Example 3, the silicon oxide particles with a particle size of less than 5 nm are replaced with silicon oxide particles with a particle size of more than 5 nm, and the rest are the same.
[0206] The positive electrode sheet obtained in Examples 1-10 and Comparative Examples 1-6 was punched into a 12 mm sheet, the diaphragm was polyethylene, and the electrolyte was 1 mol / L (LiPF6) and ethylene carbonate (EC) / dimethyl carbonate (DMC) (the volume ratio of EC and MC was 1:1) solution in an argon-protected glove box (O2<1ppm, H2O<1ppm), and the lithium sheet was used as the negative electrode to assemble a CR2032 button battery. The lithium-ion battery obtained in the above Examples and Comparative Examples was subjected to a cycle performance test, and the first discharge specific capacity at a rate of 0.1C and the first coulomb efficiency of the lithium battery were tested using a charge and discharge tester, with a voltage range of 2.75V to 4.3V; the capacity retention rate was tested at a rate of 3C for 100 and 300 cycles. Overcharge test: At room temperature, charge with 1C constant current and constant voltage for 2 hours to 150% SOC; or charge with constant voltage to 2 times the full charge cut-off voltage and then stand still. Thermal stability test: At a high temperature of 120°C, a charging voltage of 2.8V-4.2V (voltage range), and a charge and discharge rate of 0.5C, the battery capacity retention rate was tested after 100 cycles.
[0207]
[0208]
[0209]
[0210] It can be seen from the data in the table of Examples 1-10 and Comparative Examples 1-6 that the application of composite solid electrolytes in positive electrode materials not only performs well in capacity performance and rate performance, but also has significant improvements in cycle performance. At a charge and discharge rate of 0.1C, the discharge specific capacity of Examples 1-6 ranges from 186.2 to 202.6 mAh / g, of which the first discharge specific capacity of Example 6 is the highest, reaching 202.6 mAh / g. In contrast, the discharge specific capacity range of Comparative Examples 1-6 is only 100.3 to 132.3 mAh / g, which is significantly lower than that of the embodiments. In addition, the first coulombic efficiency in the embodiments is 95.6% to 98.5%, of which the first coulombic efficiency of Example 6 is the highest, reaching 98.5%, while the first coulombic efficiency in the comparative example is between 90.5% and 92.5%, which is also lower than that of the embodiments.
[0211] The overcharge test showed that during the 2-hour charging process, no smoke or fire occurred in all embodiments, while the control group had safety problems to varying degrees, which fully demonstrated the significant advantages of this solution in improving battery safety.
[0212] Under high rate charge and discharge conditions, Examples 1-6 show excellent high rate cycle stability and capacity retention compared to Comparative Examples 1-6. In particular, after 300 cycles, the capacity retention rate is as high as 90%, and under high temperature conditions (120°C), the capacity retention rate after 100 cycles is even as high as 90.6%, indicating that the cycle performance has been significantly improved.
[0213] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a composite solid electrolyte, characterized in that: include A) mixing polyethylene glycol dimethyl ether and an amine compound to obtain a mixed solution; mixing an inorganic solid electrolyte and the mixed solution for a first stirring, reaction, and drying to obtain a surface-modified LATP; the inorganic solid electrolyte is a structure of formula (I): Li 1+x Al x Ti 2-x (PO4)3、0≤x<1; B) subjecting the polyethylene glycol dimethyl ether solution, silicon oxide and lithium salt to a second stirring to obtain a PSE solution; C) subjecting the surface-modified LATP and PSE solution to a third stirring, adjusting the pH value, drying, and calcining to obtain a three-layer LATP composite structure; D) mixing the LATP composite structure of the three coating layers and the cationic polymer, and stirring to obtain a LATP composite structure with a positive charge; E) mixing the metal source, the LATP composite structure with positive charge and the organic solvent aqueous solution, heating and reducing, thereby obtaining the composite solid electrolyte.
2. The preparation method according to claim 1, characterized in that: In the step A: The particle size of the inorganic solid electrolyte is 200nm to 500nm; The first stirring time is 2 to 8 hours; The first stirring is followed by standing still, and the standing still time is 12 to 36 hours.
3. The preparation method according to claim 1, characterized in that: The polyethylene glycol dimethyl ether is obtained by polymerization of tetraethylene glycol dimethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl and triethylene glycol dimethyl ether; the molecular weight of the polyethylene glycol dimethyl ether is 250-270Da; the amine compound is ethylenediamine, ethylamine or trimethylamine; the added mass of the amine compound is 2%-6% of the polyethylene glycol dimethyl ether.
4. The preparation method according to claim 1, characterized in that: The silicon monoxide is SiO x , where 0 < x < 2 and the particle size is < 5 nm; the addition amount of the SiO x is 5-20% of the mass of LATP, and the mass ratio of silicon monoxide to PEGDME is 1:(5-30).
5. The preparation method according to claim 1, characterized in that: In the step B): The solvent of the polyethylene glycol dimethyl ether solution is one of dichloromethane and methanol; the molar ratio of the polyethylene glycol dimethyl ether solution to water is (2-5):(5-15); The selected lithium salt is one or more of LiOH·H2O, LiNO3, Li2CO3, LiBOB, LiFSI, LiC2H3O2, wherein the molar ratio of the lithium salt to silicon oxide is (5-9):(6-8); The selected second stirring time is 20 to 60 minutes and the temperature is 30 to 50°C.
6. The preparation method according to claim 1, characterized in that: In the step C): The pH value is adjusted to 7-9; the drying temperature is 70-80°C; The third stirring temperature is 40-60°C, and the stirring time is 2-5h; The calcination temperature is 400-700° C., the heating rate is 2-10° C. / h, and the calcination time is 2-6h.
7. The preparation method according to claim 1, characterized in that: Step D) The cationic polymer is selected from polyethyleneimine, polydiallyldimethylammonium chloride, chitosan or polylysine; the weight average molecular weight M of the cationic polymer is w <100kg mol -1 ; The added amount of the cationic polymer is 5 to 20% of LATP.
8. The preparation method according to claim 1, characterized in that: Step E) the metal source is an acetylacetonate metal salt; the acetylacetonate metal salt comprises a mixture of at least one acetylacetonate selected from Ni, Co, Mn, Fe, Cu, Pb, Ru and Mo and lithium acetylacetonate; the mass ratio of the mixture of at least one acetylacetonate selected from Ni, Co, Mn, Fe, Cu, Pb, Ru and Mo and lithium acetylacetonate is 1:(1-2); The mass ratio of lithium acetylacetonate to LATP is (0.3-1):1, The volume of the organic solvent aqueous solution is 100 ml, wherein the ratio of the organic solvent to water is (1-2.5): (1-2.5); The heating is performed in a gas environment, wherein the gas comprises a mixture of one of argon or nitrogen and hydrogen; The heating starts at 30°C, and the heating rate is 5-10K·min -1 , heating to 200-300° C. for reflux reaction, wherein the reflux time is 1-5 h.
9. A composite solid electrolyte, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. A positive electrode, characterized in that: The composite solid electrolyte comprises a positive electrode material, a conductive agent, a binder and the composite solid electrolyte according to claim 9.
11. A lithium ion battery, characterized in that: It comprises the positive electrode, negative electrode, separator and electrolyte as described in claim 10.
Citation Information
Patent Citations
A method for preparing a silicon / graphite / solid electrolyte composite negative electrode material
CN110858642B